1961
DOI: 10.2105/ajph.51.12.1780
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Among High School Students Related to Social Class and Parental Smoking Habits

Abstract: A study of smoking habits among high school students as related to smoking habits of their parents, and fathers' occupations revealed an increasing proportion of smokers with decreasing social class. Other aspects were studied and the authors discuss their findings with respect to other studies and future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

1964
1964
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 1 publication
0
19
0
1
Order By: Relevance
“…It is well documented that all types of smoking is a risk factor of lung cancer. Salber et al (1961) reported that smoking is the most important environmental risk factor of lung cancer. According to United States Department of Health and Human Services that 90% of all lung cancer is caused by tobacco smoking which includes all types of tobacco use such as active cigarette smoking, shisha, cigar smoking and exposure to second-hand smoke (U.S. Department of Health and Human Services, 1982;1989).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that all types of smoking is a risk factor of lung cancer. Salber et al (1961) reported that smoking is the most important environmental risk factor of lung cancer. According to United States Department of Health and Human Services that 90% of all lung cancer is caused by tobacco smoking which includes all types of tobacco use such as active cigarette smoking, shisha, cigar smoking and exposure to second-hand smoke (U.S. Department of Health and Human Services, 1982;1989).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of these studies requires caution: while familial risks are compatible with genetic predisposition, they could reflect common exposures. Smoking is the most important environmental risk factor of lung cancer, and the association between a person's smoking habits and that of his parents or siblings has been well documented (Salber and Macmahon, 1961). Unless adjustment is made for smoking habits, an above-expected incidence of lung cancer in relatives of lung cancer patients may be found, in the absence of any genetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of genetic susceptibility to lung cancer is suggested in a number of familial aggregation studies [4][5][6]8,[15][16][17][18][19] as well as in segregation analyses [20][21][22][23][24] and in a linkage study 25 Familial risks may reflect not only genetic predisposition, but also shared exposures, such as smoking habits, [27][28][29] or exposure to cooking fumes. 7,30 To address this issue, we (i) included only relatives of never-smoking probands; (ii) took into account smoking habits of the relatives, both by controlling for smoking status and by conducting analyses stratified by smoking status.…”
Section: Discussionmentioning
confidence: 99%